Otitis in Aerospace-Aerotitis: A Review - Shweta Sharma1 , Heeral Joshi1 , Pooja Anand2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Aerotitis media is a painful disorder of ear which is experienced during ascent & descent ofthe flight, caused by rapid change in external pressure leading to discomfort, pain, hearing loss, tinnitus andvertigo. It can also lead to permanent hearing loss.Objective Methods: Various research articles have been reviewed from different databases such as GoogleScholar to study the various preventive strategies which can be taken to avoid this condition during flight.Result: Valsalva maneuver is helpful in decreasing the symptoms of aerotitis media and making passengerscomfortable during the air travel.Conclusion: As aerotitis media is prevalent in ascent and descent of flight passengers, Valsalva maneuver andother preventive strategies shows beneficial effects on the symptoms of the condition through incorporatingits principles